Pengaruh Omni Channel (OCX) dan Customer Experience Terhadap Consumer Loyalty dengan Customer Satisfaction Sebagai Variabel Mediator Pada Platform Tiktok Shop - Septia Alviarni; Andala Rama Putra Barusman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The rapid growth of social commerce has significantly transformed consumer shopping behavior, particularly on social media–based platforms such as TikTok Shop. The integration of service channels (omnichannel) and the quality of customer experience are considered crucial factors in shaping customer satisfaction and loyalty. This study aims to examine the effect of Omni Channel (OCX) and Customer Experience on Consumer Loyalty, with Customer Satisfaction serving as a mediating variable among TikTok Shop users. This research adopts a quantitative approach using a survey method. Data were collected through a structured questionnaire employing a five-point Likert scale and distributed to students of the Master of Management Program at Universitas Bandar Lampung. A total of 167 respondents were selected using purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach, assisted by SmartPLS software. The findings reveal that Omni Channel and Customer Experience have positive and statistically significant effects on Customer Satisfaction and Consumer Loyalty. Customer Satisfaction also demonstrates a significant influence on Consumer Loyalty. Furthermore, mediation analysis indicates that Customer Satisfaction partially mediates the relationship between Omni Channel and Consumer Loyalty, as well as between Customer Experience and Consumer Loyalty. These results suggest that consumer loyalty is not only driven by direct channel integration and customer experience but is also strengthened through customer satisfaction. This study implies that social commerce platforms should prioritize enhancing customer experience and ensuring seamless omnichannel integration to foster customer satisfaction and long-term loyalty.